Early Identification of Pediatric Inflammatory Bowel Disease Based on a Noninvasive Multivariable Predictive Model - Wu H; Sun Y; Tang Z; Qin X; Wang Y; Huang Y (Journal of Inflammation Research)
Hailin Wu,1 Yinghua Sun,2 Zifei Tang,1 Xiaojiao Qin,2 Yuhuan Wang,1 Ying Huang1 1Department of Gastroenterology, Children’s Hospital of Fudan University, National Children’s Medical Center, Shanghai, People’s Republic of China; 2Department of Ultrasound, Children’s Hospital of Fudan University, National Children’s Medical Center, Shanghai, People’s Republic of ChinaCorrespondence: Yuhuan Wang, Department of Gastroenterology, Children’s Hospital of Fudan University, National Children’s Medical Center, No. 399 Wanyuan Road, Minhang District, Shanghai, 201102, People’s Republic of China, Tel +8664932985, Email wangyuhuan08@163.com Ying Huang, Department of Gastroenterology, Children’s Hospital of Fudan University, National Children’s Medical Center, No. 399 Wanyuan Road, Minhang District, Shanghai, 201102, People’s Republic of China, Tel +8664932985, Email yhuang815@163.comBackground: Early identification of pediatric inflammatory bowel disease (IBD) improves long-term outcomes; yet, significant diagnostic delays persist. This study aimed to establish and validate the optimal model of noninvasive evaluation tests to help clinicians with the early identification of pediatric IBD.Methods: The study adopted a retrospective development and prospective temporal validation design within the same clinical center. A cohort of 314 pediatric patients (IBD, 103; non-IBD, 211) was used to develop a logistic regression model. The model based on noninvasive features, including IBD-related symptoms, routine laboratory tests, and transabdominal ultrasound findings. Ultrasound parameters included Limberg score > 1 (bowel wall thickening with blood flow), increased mesenteric fat, disrupted wall layering, and enlarged lymph nodes. The ultrasound operator was blinded to laboratory and endoscopic results. Feature selection was performed using logistic regression and random forest methods. Model performance was assessed via bootstrapped internal validation (1000 resamples), and temporally validated in a prospective cohort of 66 children (IBD, 19; non-IBD, 47).Results: In the importance assessment, the ultrasound feature of Limberg level > 1 was identified as the most valuable feature, followed by the erythrocyte sedimentation rate, fecal calprotectin, C-reactive protein and hypoalbuminemia. The most valuable clinical symptom identified was active perianal abscess or fistula. The model, constructed from these features, demonstrated high accuracy and robustness in both internal validation (area under the curve, 0.97 [95% confidence interval: 0.95– 0.98]) and temporal external validation (area under the curve, 0.94 [95% confidence interval: 0.86– 1.00]). In the external validation set, the model showed good calibration, with a calibration slope of 0.86, and a Brier score of 0.08.Conclusion: The nomogram, based on noninvasive factors, can identify children with IBD at early stages using accessible noninvasive testing.Keywords: pediatric, inflammatory bowel disease, intestinal ultrasound, noninvasive, nomograms